Depressive Symptoms Are Associated with More Hopelessness among White than Black Older Adults - Assari, Shervin; Lankarani, Maryam Moghani (Frontiers in Public Health, 2016)
Abstract BACKGROUND: Hopelessness is a core component of depression. Our information is, however, very limited on ethnic variations in the magnitude of the link between depression and hopelessness. Using a national sample of older adults in United States, we compared Blacks and Whites for the magnitude of the association between depressive symptoms and hopelessness. METHODS: With a cross-sectional design, we used baseline data of the Religion, Aging, and Health Survey, 2001. Linear regression models were used for data analysis. Depressive symptoms (CES-D) and hopelessness were conceptualized as independent and dependent variables in different models. Demographic factors (age and gender), socio-economic status (education and marital status), and health (self-rated health) were covariates. Ethnicity was the moderator. RESULTS: In the pooled sample, higher depressive symptoms were predictive of hopelessness, above and beyond all covariates. We also found significant interactions suggesting that the association between depressive symptoms and hopelessness is weaker among Blacks compared to Whites. In ethnic- specific models, there were significant associations between depressive symptoms and hopelessness among Whites but not Blacks. CONCLUSIONS: Depressive symptoms accompany more hopelessness among Whites than Blacks. This finding may explain why Blacks with depression have a lower tendency to commit suicide. Future research should test whether or not Whites with depression better respond to psychotherapies and cognitive behavioral therapies that focus on hope enhancement. This finding may explain differential correlates of depression based on race and ethnicity.